2011
DOI: 10.1051/0004-6361/201116700
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic helicity balance during a filament eruption that occurred in active region NOAA 9682

Abstract: Context. Photospheric shear plasma flows in active regions may be responsible for the magnetic helicity injection in the solar corona not only during the energy storage process before a solar eruption, but also during and after the release of the free magnetic energy caused by the eruption. Indeed, after a filament eruption or expansion the magnetic torque imbalance can induce shear flows that can be responsible for yet another injection of magnetic helicity into the corona. Aims. We investigated the magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Later, the Eastern footpoint also showed the rotational motion and there was a jump in the positive helicity after the initiation of the filament eruption. This can be attributed to the expansion of the filament flux rope and subsequent torque imbalance as has been suggested by Parker (1974); Chae et al (2003) and observed by Smyrli et al (2010); Zuccarello et al (2011). This explains the observations of transient rotational motion in the photospheric footpoints and increased positive magnetic helicity flux after the filament eruption.…”
Section: Summary and Discussionsupporting
confidence: 63%
“…Later, the Eastern footpoint also showed the rotational motion and there was a jump in the positive helicity after the initiation of the filament eruption. This can be attributed to the expansion of the filament flux rope and subsequent torque imbalance as has been suggested by Parker (1974); Chae et al (2003) and observed by Smyrli et al (2010); Zuccarello et al (2011). This explains the observations of transient rotational motion in the photospheric footpoints and increased positive magnetic helicity flux after the filament eruption.…”
Section: Summary and Discussionsupporting
confidence: 63%
“…It has been reported that magnetic helicity was impulsively transported across the photosphere in the course of some major flares41112. The authors further noted that the impulsive helicity flux tended to decrease the magnetic helicity of the entire active region.…”
Section: Discussionmentioning
confidence: 93%
“…It is worth noting that the motion of magnetic flux could lead to the transport of magnetic helicity across the photosphere. It has been reported that, in the course of some major flares, magnetic helicity was impulsively transported across the photosphere and that the helicity flux tended to have the sign opposite to that of the active region41112. However, the type of motion pattern responsible for the impulsive helicity transport is still not understood.…”
mentioning
confidence: 99%
“… 2011 ; Zuccarello et al. 2011 ). This scenario is further supported by MHD simulations by Kusano et al.…”
Section: Long-term and Large-scale Evolution: Observational Aspectsmentioning
confidence: 99%